A comparative method for protein extraction and proteome analysis by two-dimensional gel electrophoresis from banana fruit - Surabhi, Giridara Kumar (Horticultural Biotechnology Research, 2016)
Bananas and plantains are a major staple food and export product in many countries. Banana fruit tissues contain large amounts of secondary compounds, polysaccharides and other plant polymers which will interfere with protein extraction for gel-based proteomic analysis. Due to presence of very small amount of proteins (approximately 1%) in a large matrix of fruit tissues, it classified as ‘recalcitrant’. In this connection, assessment of different protein extraction protocols and extraction of high quality proteins from banana fruit tissues is crucial for successful gel-based proteome analysis. In this study, two different protein extraction protocols were validated to isolate proteins from banana (cv.Grand Naine) fruit peel and pulp tissues, and proteins were resolved by using SDS-PAGE. A comparative study showed that phenol based method is effective in extracting proteins over TCA-acetone method. Isolated proteins were further subjected to two-dimensional gel electrophoresis separation and stained with colloidal coomassie blue to visualize protein spots. On average 380 protein spots could be detected on coomassie stained two-dimensional gel and our study clearly demonstrated the differential protein accumulation during pre-climacteric and climacteric stages of banana fruit.